Trajectories into famine: observations of patterns and implications for prevention - Daniel Maxwell; Matthew Day; Merry Fitzpatrick; Paul Howe; Peter Hailey; Anu Atre; Alex de Waal (Food Policy, 2026)

Analysis of IgG responses to Sarcocystis neurona in horses with equine protozoal myeloencephalitis (EPM) suggests a Th1-biased immune response - Catherine J. Angwin; Izabela de Assis Rocha; Stephen M. Reed; Jennifer K. Morrow; Amy Graves; Daniel K. Howe (Veterinary Immunology and Immunopathology, 2025)

Extreme Heatwave Causes Immediate, Widespread Mortality of Forest Canopy Foliage, Highlighting Modes of Forest Sensitivity to Extreme Heat - Adam Sibley; Christopher Still; Matthew Gregory; Constance Harrington; David Shaw; Nina Ferrari; Alex Dye; Mark Schulze; Glenn Howe; David E. Rupp; Christopher Daly; Daniel DePinte; et al. (Global Change Biology, 2025)
In late June 2021, multiple days of record‐breaking heat caused an unprecedented amount of foliage death in the forests of the Pacific Northwest, USA. Portions of tree canopies with healthy green foliage prior to the heat changed to red or orange shortly after the event. The change in foliage color could be readily seen in satellite imagery and was corroborated as foliar death (heat scorch) by aerial surveys and extensive observations on the ground. To better understand the patterns and processes driving foliar death, we used satellite imagery to identify 293,546 ha of forest, or ~4.7% of forest area, that were damaged in western Oregon and Washington by this extreme heat event. Analysis of underlying drivers of the observed heat damage indicated greater sensitivity was related to abiotic factors such as sun exposure, aspect, and microclimate, as well as biotic factors like tree species and stand age, budburst phenology, and foliar pathogens impacting tree health. Iconic, culturally and economically significant species like western redcedar, western hemlock, and Sitka spruce were disproportionately sensitive to heat damage, including in old‐growth stands where they are canopy dominants. These findings highlight the multifaceted challenges posed to forests by extreme heat waves, and the need to better understand their impact on forest ecosystems in a rapidly warming climate.

Embryotoxicity of statins and other prescribed drugs with reported off-target effects on cholesterol biosynthesis - Taryn Hartley; Hagir Abdelmagid; Zeenat Abdulsalam; Aliyah Mansion; Emily Howe; Daniel Ramirez; Kaylei White; Emmanuel Tadjuidje (Reproductive Toxicology, 2025)

The potential of selected shade tree species for managing mirids and black pod disease infection in cocoa agroforestry systems in Ghana - Bismark Kwesi Asitoakor; Anders Ræbild; Richard Asare; Philippe Vaast; Andy G. Howe; Vincent Yao Eziah; Kwadwo Owusu; Eric Opoku Mensah; Daniel Ashie Kotey; Hans Peter Ravn (Crop Protection, 2024)

Mitigating municipal solid waste fouling in biofuel conversion via screw surface modifications - Xin He; Jens T. Darsell; Jaya Shankar Tumuluru; Wenbo Wang; Harry M. Meyer; James R. Keiser; Aashish Rohatgi; Daniel T. Howe; Jun Qu (Biomass and Bioenergy, 2024)

The frequency and chemical phenotype of neighboring plants determine the effects of intraspecific plant diversity - Andrea E. Glassmire; Kayleigh C. Hauri; Daniel B. Turner; Luke N. Zehr; Koichi Sugimoto; Gregg A. Howe; William C. Wetzel (Ecology, 2024)
Associational effects, whereby plants influence the biotic interactions of their neighbors, are an important component of plant–insect interactions. Plant chemistry has been hypothesized to mediate these interactions. The role of chemistry in associational effects, however, has been unclear in part because the diversity of plant chemistry makes it difficult to tease apart the importance and roles of particular classes of compounds. We examined the chemical ecology of associational effects using backcross‐bred plants of the Solanum pennellii introgression lines. We used eight genotypes from the introgression line system to establish 14 unique neighborhood treatments that maximized differences in acyl sugars, proteinase inhibitor, and terpene chemical diversity. We found that the chemical traits of the neighboring plant, rather than simply the number of introgression lines within a neighborhood, influenced insect abundance on focal plants. Furthermore, within‐chemical class diversity had contrasting effects on herbivore and predator abundances, and depended on the frequency of neighboring plant chemotypes. Notably, we found insect mobility—flying versus crawling—played a key role in insect response to phytochemistry. We highlight that the frequency and chemical phenotype of plant neighbors underlie associational effects and suggest this may be an important mechanism in maintaining intraspecific phytochemical variation within plant populations.

The unexpected influence of legacy conspecific density dependence - Lukas J. Magee; Joseph A. LaManna; Amy T. Wolf; Robert W. Howe; Yuanming Lu; Denis Valle; Daniel J. B. Smith; Robert Bagchi; David Bauman; Daniel J. Johnson (Ecology Letters, 2024)
When plants die, neighbours escape competition. Living conspecifics could disproportionately benefit because they are freed from negative intraspecific processes; however, if the negative effects of past conspecific neighbours persist, other species might be advantaged, and diversity might be maintained through legacy effects. We examined legacy effects in a mapped forest by modelling the survival of 37,212 trees of 23 species using four neighbourhood properties: living conspecific, living heterospecific, legacy conspecific (dead conspecifics) and legacy heterospecific densities. Legacy conspecific effects proved nearly four times stronger than living conspecific effects; changes in annual survival associated with legacy conspecific density were 1.5% greater than living conspecific effects. Over 90% of species were negatively impacted by legacy conspecific density, compared to 47% by living conspecific density. Our results emphasize that legacies of trees alter community dynamics, revealing that prior research may have underestimated the strength of density dependent interactions by not considering legacy effects.

Effects of swine manure dilution with lagoon effluent on microbial communities and odor formation in pit recharge systems - Okhwa Hwang; Bryan Emmett; Daniel Andersen; Adina Howe; Kyoung Ro; Steven Trabue (Journal of Environmental Management, 2024)

Managing offshore multi-use settings: Use of conceptual mapping to reduce uncertainty of co-locating seaweed aquaculture and wind farms - Ryan O'Shea; Elisa Capuzzo; Victoria Hemming; Gretchen Grebe; Rick Stafford; Sander W.K. van den Burg; Daniel Wood; Gordon Watson; Victoria Wells; Teresa Johnson; Stefan Erbs; Jaap W. van Hal; et al. (Journal of Environmental Management, 2024)

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

Addressing the welfare needs of farmed lumpfish: Knowledge gaps, challenges and solutions - Carlos Garcia de Leaniz; Carolina Gutierrez Rabadan; Sara I. Barrento; Rebecca Stringwell; Paul N. Howes; Ben A. Whittaker; Jessica F. Minett; Robert G. Smith; Craig L. Pooley; Ben J. Overland; Leigh Biddiscombe; Richard Lloyd; et al. (Reviews in Aquaculture, 2022)
Lumpfish ( Cyclopterus lumpus L.) are increasingly being used as cleaner fish to control parasitic sea lice, one of the most important threats to salmon farming. However, lumpfish cannot survive feeding solely on sea lice, and their mortality in salmon net‐pens can be high, which has welfare, ethical and economic implications. The industry is under increasing pressure to improve the welfare of lumpfish, but little guidance exists on how this can be achieved. We undertook a knowledge gap and prioritisation exercise using a Delphi approach with participants from the fish farming sector, animal welfare, academia and regulators to assess consensus on the main challenges and potential solutions for improving lumpfish welfare. Consensus among participants on the utility of 5 behavioural and 12 physical welfare indicators was high (87–89%), reliable (Cronbach's alpha = 0.79, 95CI = 0.69–0.92) and independent of participant background. Participants highlighted fin erosion and body damage as the most useful and practical operational welfare indicators, and blood parameters and behavioural indicators as the least practical. Species profiling revealed profound differences between Atlantic salmon and lumpfish in relation to behaviour, habitat preferences, nutritional needs and response to stress, suggesting that applying a common set of welfare standards to both species cohabiting in salmon net‐pens may not work well for lumpfish. Our study offers 16 practical solutions for improving the welfare of lumpfish and illustrates the merits of the Delphi approach for achieving consensus among stakeholders on welfare needs, targeting research where is most needed and generating workable solutions.

Examining the impact of the Great Barrier Reef on tsunami propagation using numerical simulations - Mandi C. Thran; Sascha Brune; Jody M. Webster; Dale Dominey-Howes; Daniel Harris (Natural Hazards, 2021)

Correction to: Is population structure in the genetic biobank era irrelevant, a challenge, or an opportunity? - Daniel John Lawson; Neil Martin Davies; Simon Haworth; Bilal Ashraf; Laurence Howe; Andrew Crawford; Gibran Hemani; George Davey Smith; Nicholas John Timpson (Human Genetics, 2020)

Is population structure in the genetic biobank era irrelevant, a challenge, or an opportunity? - Daniel John Lawson; Neil Martin Davies; Simon Haworth; Bilal Ashraf; Laurence Howe; Andrew Crawford; Gibran Hemani; George Davey Smith; Nicholas John Timpson (Human Genetics, 2020)

Direct Measurements of Bed Shear Stress under Swash Flows on Steep Laboratory Slopes at Medium to Prototype Scales - Daniel Howe; Chris E. Blenkinsopp; Ian L. Turner; Tom E. Baldock; Jack A. Puleo (Journal of Marine Science and Engineering, 2019)
Robust measurements of bed shear stress under wave runup flows are necessary to inform beachface sediment transport modelling. In this study, direct measurements of swash zone bed shear stress were obtained in medium and prototype-scale laboratory experiments on steep slopes. Peak shear stresses coincided with the arrival of uprush swash fronts and high-resolution measurement of swash surface profiles indicated a consistently seaward sloping swash surface with minimal evidence of a landward sloping swash front. The quadratic stress law was applied to back-calculate time-varying friction factors, which were observed to decrease with increasing Reynolds number on smooth slopes, consistent with theory for steady flows. Additionally, friction factors remained relatively constant throughout the swash cycle (except around flow reversal), with a variation of approximately ±20% from the mean value and with only small differences between uprush and backwash. Measured friction factors were observed to be larger than expected when plotted on the Moody or wave friction diagram for a given Reynolds number and relative roughness, consistent with previous field and laboratory studies at various scales.

Global Observing Needs in the Deep Ocean - Lisa A. Levin; Brian J. Bett; Andrew R. Gates; Patrick Heimbach; Bruce M. Howe; Felix Janssen; Andrea McCurdy; Henry A. Ruhl; Paul Snelgrove; Karen I. Stocks; David Bailey; Simone Baumann-Pickering; et al. (Frontiers in Marine Science, 2019)

Front Cover - James A. Lutz; Tucker J. Furniss; Daniel J. Johnson; Stuart J. Davies; David Allen; Alfonso Alonso; Kristina J. Anderson‐Teixeira; Ana Andrade; Jennifer Baltzer; Kendall M. L. Becker; Erika M. Blomdahl; Norman A. Bourg; et al. (Global Ecology and Biogeography, 2018)

Global importance of large‐diameter trees - James A. Lutz; Tucker J. Furniss; Daniel J. Johnson; Stuart J. Davies; David Allen; Alfonso Alonso; Kristina J. Anderson‐Teixeira; Ana Andrade; Jennifer Baltzer; Kendall M. L. Becker; Erika M. Blomdahl; Norman A. Bourg; et al. (Global Ecology and Biogeography, 2018)
Aim To examine the contribution of large‐diameter trees to biomass, stand structure, and species richness across forest biomes. Location Global. Time period Early 21st century. Major taxa studied Woody plants. Methods We examined the contribution of large trees to forest density, richness and biomass using a global network of 48 large (from 2 to 60 ha) forest plots representing 5,601,473 stems across 9,298 species and 210 plant families. This contribution was assessed using three metrics: the largest 1% of trees ≥ 1 cm diameter at breast height (DBH), all trees ≥ 60 cm DBH, and those rank‐ordered largest trees that cumulatively comprise 50% of forest biomass. Results Averaged across these 48 forest plots, the largest 1% of trees ≥ 1 cm DBH comprised 50% of aboveground live biomass, with hectare‐scale standard deviation of 26%. Trees ≥ 60 cm DBH comprised 41% of aboveground live tree biomass. The size of the largest trees correlated with total forest biomass ( r 2 = .62, p r 2 = .45, p r 2 = .33, p r 2 = .17, p = .002). The concentration of biomass in the largest 1% of trees declined with increasing absolute latitude ( r 2 = .46, p r 2 = .31, p r 2 = .26, p Main conclusions Because large‐diameter trees constitute roughly half of the mature forest biomass worldwide, their dynamics and sensitivities to environmental change represent potentially large controls on global forest carbon cycling. We recommend managing forests for conservation of existing large‐diameter trees or those that can soon reach large diameters as a simple way to conserve and potentially enhance ecosystem services.

The role of functional uniqueness and spatial aggregation in explaining rarity in trees - María Natalia Umaña; Xiangcheng Mi; Min Cao; Brian J. Enquist; Zhanqing Hao; Robert Howe; Yoshiko Iida; Daniel Johnson; Luxiang Lin; Xiaojuan Liu; Keping Ma; I‐Fang Sun; et al. (Global Ecology and Biogeography, 2017)
Aim Determining the drivers of species rarity is fundamental for understanding and conserving biodiversity. Rarity of a given species within its community may arise due to exclusion by other ecologically similar species. Conversely, rare species may occupy habitats that are rare in the landscape or they may be ill‐suited to all available habitats. The first mechanism would lead to common and rare species occupying similar ecological space defined by functional traits. The second mechanism would result in common and rare species occupying dissimilar ecological space and spatial aggregation of rare species, either because they are specialists in rare habitats or because rare species tend to be dispersal limited. Here, we quantified the contribution of locally rare species to community functional richness and the spatial aggregation of species across tree communities world‐wide to address these hypotheses. Location Asia and the Americas. Time period 2002 to 2012 (period that considers the censuses for the plots used). Major taxa studied Angiosperm and Gymnosperm trees. Methods We compiled a dataset of functional traits from all the species present in eight tree plots around the world to evaluate the contribution of locally rare species to tree community functional richness using multi‐ and univariate approaches. We also quantified the spatial aggregation of individuals within species at several spatial scales as it relates to abundance. Results Locally rare tree species in temperate and tropical forests tended to be functionally unique and are consistently spatially clustered. Furthermore, there is no evidence that this pattern is driven by pioneer species being locally rare. Main conclusions This evidence shows that locally rare tree species disproportionately contribute to community functional richness, and we can therefore reject the hypothesis that locally rare species are suppressed by ecologically similar, but numerically dominant, species. Rather, locally rare species are likely to be specialists on spatially rare habitats or they may be ill‐suited to the locally available environments.

Targeting glutamate to treat schizophrenia: lessons from recent clinical studies - Katherine Beck; Daniel C Javitt; Oliver D Howes (Psychopharmacology, 2016)

Tree‐mycorrhizal associations detected remotely from canopy spectral properties - Joshua B. Fisher; Sean Sweeney; Edward R. Brzostek; Tom P. Evans; Daniel J. Johnson; Jonathan A. Myers; Norman A. Bourg; Amy T. Wolf; Robert W. Howe; Richard P. Phillips (Global Change Biology, 2016)
A central challenge in global ecology is the identification of key functional processes in ecosystems that scale, but do not require, data for individual species across landscapes. Given that nearly all tree species form symbiotic relationships with one of two types of mycorrhizal fungi – arbuscular mycorrhizal ( AM ) and ectomycorrhizal ( ECM ) fungi – and that AM ‐ and ECM ‐dominated forests often have distinct nutrient economies, the detection and mapping of mycorrhizae over large areas could provide valuable insights about fundamental ecosystem processes such as nutrient cycling, species interactions, and overall forest productivity. We explored remotely sensed tree canopy spectral properties to detect underlying mycorrhizal association across a gradient of AM ‐ and ECM ‐dominated forest plots. Statistical mining of reflectance and reflectance derivatives across moderate/high‐resolution Landsat data revealed distinctly unique phenological signals that differentiated AM and ECM associations. This approach was trained and validated against measurements of tree species and mycorrhizal association across ~130 000 trees throughout the temperate United States. We were able to predict 77% of the variation in mycorrhizal association distribution within the forest plots ( P

Editorial: Reporting guidelines for psychopharmacology - Thomas Steckler; H. Valerie Curran; Harriet de Wit; Oliver Howes; Daniel Hoyer; Irwin Lucki; Klaus A. Miczek; A. Leslie Morrow; Lawrence H. Price; Trevor W. Robbins (Psychopharmacology, 2016)

CTFS ‐Forest GEO : a worldwide network monitoring forests in an era of global change - Kristina J. Anderson‐Teixeira; Stuart J. Davies; Amy C. Bennett; Erika B. Gonzalez‐Akre; Helene C. Muller‐Landau; S. Joseph Wright; Kamariah Abu Salim; Angélica M. Almeyda Zambrano; Alfonso Alonso; Jennifer L. Baltzer; Yves Basset; Norman A. Bourg; et al. (Global Change Biology, 2015)
Global change is impacting forests worldwide, threatening biodiversity and ecosystem services including climate regulation. Understanding how forests respond is critical to forest conservation and climate protection. This review describes an international network of 59 long‐term forest dynamics research sites ( CTFS ‐Forest GEO ) useful for characterizing forest responses to global change. Within very large plots (median size 25 ha), all stems ≥1 cm diameter are identified to species, mapped, and regularly recensused according to standardized protocols. CTFS ‐Forest GEO spans 25°S–61°N latitude, is generally representative of the range of bioclimatic, edaphic, and topographic conditions experienced by forests worldwide, and is the only forest monitoring network that applies a standardized protocol to each of the world's major forest biomes. Supplementary standardized measurements at subsets of the sites provide additional information on plants, animals, and ecosystem and environmental variables. CTFS ‐Forest GEO sites are experiencing multifaceted anthropogenic global change pressures including warming (average 0.61 °C), changes in precipitation (up to ±30% change), atmospheric deposition of nitrogen and sulfur compounds (up to 3.8 g N m −2 yr −1 and 3.1 g S m −2 yr −1 ), and forest fragmentation in the surrounding landscape (up to 88% reduced tree cover within 5 km). The broad suite of measurements made at CTFS ‐Forest GEO sites makes it possible to investigate the complex ways in which global change is impacting forest dynamics. Ongoing research across the CTFS ‐Forest GEO network is yielding insights into how and why the forests are changing, and continued monitoring will provide vital contributions to understanding worldwide forest diversity and dynamics in an era of global change.

Assessing S ymbiodinium diversity in scleractinian corals via next‐generation sequencing‐based genotyping of the ITS2 rDNA region - Chatchanit Arif; Camille Daniels; Till Bayer; Eulalia Banguera‐Hinestroza; Adrian Barbrook; Christopher J. Howe; Todd C. LaJeunesse; Christian R. Voolstra (Molecular Ecology, 2014)
The persistence of coral reef ecosystems relies on the symbiotic relationship between scleractinian corals and intracellular, photosynthetic dinoflagellates in the genus Symbiodinium . Genetic evidence indicates that these symbionts are biologically diverse and exhibit discrete patterns of environmental and host distribution. This makes the assessment of Symbiodinium diversity critical to understanding the symbiosis ecology of corals. Here, we applied pyrosequencing to the elucidation of Symbiodinium diversity via analysis of the internal transcribed spacer 2 ( ITS 2) region, a multicopy genetic marker commonly used to analyse Symbiodinium diversity. Replicated data generated from isoclonal Symbiodinium cultures showed that all genomes contained numerous, yet mostly rare, ITS 2 sequence variants. Pyrosequencing data were consistent with more traditional denaturing gradient gel electrophoresis ( DGGE ) approaches to the screening of ITS 2 PCR amplifications, where the most common sequences appeared as the most intense bands. Further, we developed an operational taxonomic unit ( OTU )‐based pipeline for Symbiodinium ITS 2 diversity typing to provisionally resolve ecologically discrete entities from intragenomic variation. A genetic distance cut‐off of 0.03 collapsed intragenomic ITS 2 variants of isoclonal cultures into single OTU s. When applied to the analysis of field‐collected coral samples, our analyses confirm that much of the commonly observed Symbiodinium ITS 2 diversity can be attributed to intragenomic variation. We conclude that by analysing Symbiodinium populations in an OTU ‐based framework, we can improve objectivity, comparability and simplicity when assessing ITS 2 diversity in field‐based studies.

Conspecific negative density‐dependent mortality and the structure of temperate forests - Daniel J. Johnson; Norman A. Bourg; Robert Howe; William J. McShea; Amy Wolf; Keith Clay (Ecology, 2014)
Factors that control tree seedling dynamics are critical determinants of forest diversity. We examined the role of density‐dependent mortality and abiotic factors in the differential establishment and survival of tree seedlings at three, large, mapped forest plots in Indiana, Virginia, and Wisconsin, USA. We tested whether seedling densities and seedling survival are related to local biotic and abiotic factors with generalized linear mixed models. Spatial point pattern analyses were utilized to determine if the distribution patterns of seedlings and saplings are consistent with a pattern generated by negative density‐dependent mortality with respect to conspecific trees. Initial sampled seedling density for nearly a third of species showed a positive correlation with increasing conspecific basal area, indicating dispersal limitation, but few had any association with abiotic variables. By contrast, survival of seedlings over one year significantly declined with increasing conspecific basal area. Point pattern analyses indicated that nearly one‐third of tree species had significantly over‐dispersed point patterns of conspecific seedlings and saplings relative to adult densities; the majority of other species exhibited random spatial arrangements. Our results demonstrate that negative conspecific density‐dependent mortality of seedlings could generate the spatial patterns observed at later life stages. By differentially favoring seedlings of other species, this process may contribute to the maintenance of tree diversity in temperate forests, just as others have demonstrated for tropical forests.

Re‐evaluation of the Roseau Tuff eruptive sequence and other ignimbrites in Dominica, Lesser Antilles - TRACY M. HOWE; JAN M. LINDSAY; PHIL SHANE; AXEL K. SCHMITT; DANIEL F. STOCKLI (Journal of Quaternary Science, 2014)
The island of Dominica hosts several ignimbrites, including the Roseau Tuff, thought to represent the largest eruption in the Caribbean in the past 200 000 years. The volcanic stratigraphy of the island is poorly understood due to limited outcrops and a paucity of geochemical and geochronological data. The discovery of a new fully accessible exposure of three ignimbrites intercalated with paleosols provides an opportunity to re‐evaluate the current stratigraphic framework of ignimbrite‐forming eruptions on the island. Whole‐rock analyses of pumice clasts from Dominica ignimbrites are andesitic (61–66% SiO 2 ) and in most cases are geochemically indistinguishable. Ignimbrites in the north of the island have less evolved glass compositions (73–75% SiO 2 ) and more mafic orthopyroxene compositions (En > 56) than their southern counterparts (75–78% SiO 2 ; En

Premorbid diet in relation to survival from prostate cancer (Canada) - Daniel J. Kim; Richard P. Gallagher; T. Gregory Hislop; Eric J. Holowaty; Geoffrey R. Howe; Meera Jain; John R. McLaughlin; Chong-Ze Teh; Thomas E. Rohan (Cancer Causes & Control, 2000)